2017
DOI: 10.1002/bdd.2091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proton pump inhibitors and famotidine on elimination of plasma methotrexate: Evaluation of drug–drug interactions mediated by organic anion transporter 3

Abstract: Methotrexate (MTX) is an antifolate agent used in the treatment of numerous types of cancer, and eliminated by active tubular secretion via organic anion transporter 3 (OAT3). Gastric antisecretory drugs, such as proton pump inhibitors (PPIs) and histamine H receptor antagonists, are widely used among patients with cancer in clinical practice. The aim of the present study was to analyse the potential drug-drug interactions between MTX and gastric antisecretory drugs in high-dose MTX (HD-MTX) therapy. The impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
(65 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, (S)-lansoprazole inhibited hOAT3-mediated transport of pemetrexed and methotrexate more strongly than the corresponding (R)-lansoprazole (Table 2). The inhibitory effect of (S)-lansoprazole against hOAT3-mediated transport of pemetrexed and methotrexate was comparable to the results in the several previous reports with racemic lansoprazole [11, 15, 36]. In contrast, the inhibitory effect against hOAT1 did not show stereoselectivity (Table 1).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, (S)-lansoprazole inhibited hOAT3-mediated transport of pemetrexed and methotrexate more strongly than the corresponding (R)-lansoprazole (Table 2). The inhibitory effect of (S)-lansoprazole against hOAT3-mediated transport of pemetrexed and methotrexate was comparable to the results in the several previous reports with racemic lansoprazole [11, 15, 36]. In contrast, the inhibitory effect against hOAT1 did not show stereoselectivity (Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, the ratio of unbound C max to IC 50 value of (S)-lansoprazole against hOAT3 in PM of CYP2C19 was ≥0.1, suggesting a clinical interaction between (S)-lansoprazole and hOAT3 substrates in PM (data not shown). Indeed, the delayed elimination of methotrexate (hOAT3 substrate) was observed in patients receiving racemic lansoprazole [12-14, 36]. Miura et al [38] demonstrated that the pharmacokinetics of (S)-lansoprazole were more intensely affected by ­ CYP2C19 polymorphism than those of (R)-lansoprazole, suggesting that (S)-lansoprazole is responsible for individual variations of lansoprazole-induced drug interactions associated with hOAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Around 80% of MTX is primarily excreted via the kidney in its unchanged form with transporter-mediated secretion prevailing over glomerular filtration. Notably, case reports of life-threatening kidney failure were reported after coadministration of MTX with probenecid, NSAIDs, or proton pump inhibitors, which supports an involvement of the OATs in tubular handling of MTX [111][112][113][114].…”
Section: Oatp1a2mentioning
confidence: 86%
“…However, the impact of efflux transporter (OAT3) inhibition in renal tubules and/or in the blood brain barrier deserves an investigation [for a review on OAT family, ( 36 , 37 )]. Several compounds such as probenecid and proton pump inhibitors have been described to inhibit OAT3 transport which increases plasma and brain concentrations ( 38 , 39 ). It could be of interest to combine baclofen with an OAT3 inhibitor to investigate if brain and plasma concentrations are increased and if it is associated with an improvement of the clinical effect.…”
Section: Discussionmentioning
confidence: 99%